Legal Politics Of Job Creation Law Number 6 Of 2023 Concerning Workers' Rights To Wages - Mulia, Rafel Putra (PALAR (Pakuan Law review), 2025)
AbstractThe formation of laws and regulations should ideally uphold the principles of participation, transparency, and accountability. However, these principles came under scrutiny during the legislative process of Law No. 11 of 2020 on Job Creation, which was enacted through the omnibus law method by the Government and the House of Representatives. The rapid deliberation process, lack of public participation, and substantial changes in content triggered widespread controversy and constitutional challenges. The Constitutional Court, in Decision No. 91/PUU-XVIII/2020, declared the law conditionally unconstitutional and granted a two-year period for revision. In response, the Government issued Government Regulation in Lieu of Law (Perppu) No. 2 of 2022, which was later ratified as Law No. 6 of 2023. This study aims to analyze the legislative process of the Job Creation Law from the perspective of constitutional law and the principles of sound regulatory drafting. Using a normative juridical approach, the study finds that the main issues lie in the lack of public engagement and procedural inconsistencies, which ultimately affect the law’s legitimacy and enforceability. Keywords: Job Creation Law; Constitutional Court; Legislative Process; Public Participation; Legal Reform.